Antimicrobial activities of Eugenol and Cinnamaldehyde against the human gastric pathogen Helicobacter pylori - Ahmed Khaja S; Musaddiq M; Ahmed Irshad; Khan Aleem A; Ali Shaik; Polasa H; Rao L Venkateswar; Habibullah Chittoor M; Sechi Leonardo A; Ahmed Niyaz (BMC, 2005)
Abstract Background Eradication of Helicobacter pylori is an important objective in overcoming gastric diseases. Many regimens are currently available but none of them could achieve 100% success in eradication. Eugenol and cinnamaldehyde that are commonly used in various food preparations are known to possess antimicrobial activity against a wide spectrum of bacteria. Aim The present study was performed to assess the in vitro effects of eugenol and cinnamaldehyde against indigenous and standard H. pylori strains, their minimum inhibitory concentrations (MICs) and time course lethal effects at various pH. Methods A total of 31 strains (29 indigenous and one standard strain of H. pylori ATCC 26695, one strain of E. coli NCIM 2089) were screened. Agar dilution method was used for the determination of drug sensitivity patterns of isolates to the commonly used antibiotics and broth dilution method for the test compounds. Results Eugenol and cinnamaldehyde inhibited the growth of all the 30 H. pylori strains tested, at a concentration of 2 μg/ml, in the 9th and 12th hours of incubation respectively. At acidic pH, increased activity was observed for both the compounds. Furthermore, the organism did not develop any resistance towards these compounds even after 10 passages grown at sub-inhibitory concentrations. Conclusion These results indicate that the two bioactive compounds we tested may prevent H. pylori growth in vitro, without acquiring any resistance.